Electrochemical and metallurgical characterization of ZrCr1-xNiMox AB2 metal hydride alloys - Erika, Teliz (2015)
The effects of partial replacement of chromium by molybdenum was studied on the structure and electrochemical kinetic properties of ZrCr1-xNiMox(x = 0.0, 0.3 and 0.6) metal hydride alloys. The arc-melting prepared alloys were metallurgically characterized by X-ray diffraction and energy dispersive spectroscopy microanalysis, which showed AB2 (with hexagonal C14 structure) and ZrxNiy (Zr7Ni10, Zr9Ni11) phases. After a partial substitution of chromium by molybdenum, secondary phases monotonically increase with the C14 unit cell volume indicating that most of molybdenum atoms locate in the B-site. The alloys were electrochemically characterized using charge/discharge cycling, electrochemical impedance spectroscopy and rate capability experiments that allowed the determination of hydriding reaction kinetic parameters. The presence of molybdenum produces a positive effect for hydrogen diffusion in the alloy lattice, and ZrCr0.7NiMo0.3 alloy depicts the better kinetics associated with a fast activation, lower charge transfer resistance and the best high rate discharge behavior. This fact would be related to a lower diffusion time constant and a bigger value of the product between exchange density current and surface active area. There is a trade-off in the amounts of secondary phase and Laves phases in order to improve the kinetic performance.